ELECTRIC VEHICLE TECHNOLOGY: CHARACTERISTICS, DEVELOPMENT AND PROSPECTS - Yashar Badalov (Theoretical Hypotheses and Empirical Results, 2024)
The increase in the world’s population brings with it traffic problems, and the number of vehicles on the roads is increasing day by day. The increase in the number of cars with internal combustion engines has also increased the amount of harmful gases released into the environment. This situation has negatively affected the quality of the environment and led to different energy sources for the performance of the car. Adding to the fact that future oil reserves will run out, the demand for electric cars has increased even more. As it can be seen, taking into account the importance and relevance of the topic in our modern times, the research carried out on this topic will make it possible to achieve the goal. The article analyzes the characteristics, advantages and disadvantages of electric cars, as well as comparisons with hybrid and full-fuel vehicles. This study examines the early development history of electric vehicles, current models and latest technologies, types of battery charging stations and electric motors used, and includes expectations and predictions for the future of the entire system.